2020
DOI: 10.33545/gynae.2020.v4.i3d.606
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of cerebro-placental ratio in antenatal surveillance

Abstract: Background: Cerebro-placental ratio (CPR) with a threshold value of less than 1.08 has been suggested to closely reflect acute changes in pO2, indicating fetal hypoxia in IUGR. Objective: The objective of the study was to evaluate the sensitivity and specificity of CPR in clinically diagnosed cases of IUGR and to predict adverse perinatal outcome in cases of abnormal CPR. Setting: The study was conducted at a tertiary care hospital. Materials and Methods: One hundred and twenty consecutive clinically suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This finding was comparable to the statistically significant relation noted by Singh et al, 2013 [18] with 61.5% caesarean deliveries in their study though. Furthermore, Ganju, 2020 [19] reported that abnormal CPR is significantly associated with caesarean delivery (p value=0.001). Gruettner and his co-workers, 2019 [13] found that in their cases 41.2% of the patients had a spontaneous delivery, whereas 9.6% had a vaginal operative delivery and 49.3% underwent a cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was comparable to the statistically significant relation noted by Singh et al, 2013 [18] with 61.5% caesarean deliveries in their study though. Furthermore, Ganju, 2020 [19] reported that abnormal CPR is significantly associated with caesarean delivery (p value=0.001). Gruettner and his co-workers, 2019 [13] found that in their cases 41.2% of the patients had a spontaneous delivery, whereas 9.6% had a vaginal operative delivery and 49.3% underwent a cesarean section.…”
Section: Discussionmentioning
confidence: 99%